A Patient with Hypercalcemia Who Turned Out to Have Multiple Endocrine Disorders - Z, Alamer; K, Baagar; Z, Rohani; M, Zirie (Archives of Clinical and Medical Case Reports, 2021)
Multiple endocrine neoplasia type 1 (MEN1) is rare and characterized by 3 main endocrine tumors (parathyroid, enteropancreatic, and pituitary). We report a patient with MEN1 and present a comprehensive literature review. A 30- year-old man presented with abdominal pain. He was vitally stable, dehydrated with coarse facial features, nodular goiter, and trunk neurofibroma-like lesions. Laboratory showed normal amylase and lipase, calcium 3.2 (2.20-2.55 mmol/L), phosphorous 0.67 (0.81-1.45 mmol/l), and PTH 400 (15-65 ng/L). He received intravenous saline, calcitonin, and zoledronate. During hospitalization, he developed hypoglycemia 1.6 mmol/L with C-peptide 5.48 (1.10-4.4 ng/mL), and insulin 22.8 (2.6-24.9 mcunit/mL). Sestamibi scan revealed parathyroid gland hyperplasia. MRI abdomen showed a pancreatic lesion suggestive of insulinoma. He had prolactin > 100000 (85-323 mIU/L), IGF-1 456 (96-228 ug/L), secondary hypogonadism and secondary hypothyroidism. Pituitary MRI showed giant macroadenoma. MEN1 was clinically diagnosed and confirmed by genetic testing. Thyroid nodules FNA showed follicular neoplasm. The multidisciplinary team recommended cabergoline, insulinoma surgery, and total thyroidectomy plus total parathyroidectomy with autoimplantation of the parathyroid. Histopathology confirmed a well-differentiated pancreatic neuroendocrine tumor, and a 9 mm Papillary Thyroid Cancer (PTC) (pT1aN0). Thereafter, He had no hypoglycemia; however, he developed hypoparathyroidism. We kept him on thyroxine, calcitriol, and calcium and monitored his response to cabergoline. MEN1 can be diagnosed genetically, or clinically by having 2 of the main 3 tumors or 1 tumor in a first-degree relative of a MEN1 patient. Genetic testing is essential for index cases and unaffected at-risk relatives to decide further screening. The MEN1 individual lesions management is generally similar to sporadic cases; however, patient